Penilaian Kualitas Estetika pada Rifan Coffee di Kota Sabang - Diky Hendrawan; Zulhadi Sahputra; Mirza Mirza; Muhammad Heru Arie Edytia (Jurnal RAUT, 2022)
A cafe is a place to eat and drink and also a place to gather that is popular among young people. A cafe's aesthetic quality can affect the number of visitors who come. Rifan Coffee is one of the cafes located in the coastal area and has a beautiful view in Sabang, Aceh. However, the cafe is less attractive and aesthetic when viewed from a design perspective. This presumption encourages the author to examine the aesthetic qualities of the cafe. The method used in this research is descriptive qualitative. The assessment uses a Likert scale. The author himself acts as an observer and giver of values based on theories related to aesthetics. The variables assessed are space-forming elements and space-filling elements, which are floors, walls, ceilings, furniture, and vegetation. The results showed that the aesthetic quality of the cafe has a value of 1 to 3, which means it has a very low to moderate aesthetic quality. Therefore, the authors provide design solutions to be considered in the redesign